Dextran sulphate induces fibrinogen receptor activation through a novel Syk-independent PI-3 kinase-mediated tyrosine kinase pathway in platelets - Getz, Todd M.; Manne, Bhanu Kanth; Buitrago, Lorena; Mao, Yingying; Kunapuli, Satya P. (Thrombosis and Haemostasis, 2013)
In our attempt to find a physiological agonist that activates PAR3 receptors, we screened several coagulation proteases using PAR4 null platelets. We observed that FXIIa and heat inactivated FXIIa, but not FXII, caused platelet aggregation. We have identified a contaminant activating factor in FXIIa preparation as dextran sulfate (DxS), which caused aggregation of both human and mouse platelets. DxS-induced platelet aggregation was unaffected by YM254890, a Gq inhibitor, but abolished by pan-Src family kinase (SFK) inhibitor PP2, suggesting a role for SFKs in this pathway. However, DxS-induced platelet aggregation was unaffected in FcRγ-chain null murine platelets, ruling out the possibility of glycoprotein VI-mediated events. More interesting, OXSI-2 and Go6976, two structurally unrelated inhibitors shown to affect Syk, had only a partial effect on DxS-induced PAC-1 binding. DxS-induced platelet aggregation and intracellular calcium increases were abolished by the pan PI-3 kinase inhibitor LY294002, or an isoform-specific PI-3 kinase β inhibitor TGX-221. Pretreatment of platelets with Syk inhibitors or ADP receptor antagonists had little effect on Akt phosphorylation following DxS stimulation. These results, for the first time, establish a novel tyrosine kinase pathway in platelets that causes fibrinogen receptor activation in a PI-3 kinase-dependent manner without a crucial role for Syk.
Keywords: Platelets; signalling; dextran-sulfate; Src-Family kinases; Syk kinase; PI-3 kinase